Bioaccumulation of Selected Halogenated Organic Flame Retardants in Lake Ontario - Kurt Karakuş, Perihan Binnur; Muir, Derek C. G.; de Jourdan, Benjamin; Teixeira, Camilla; Martindale, Jessica Epp; Embers, Heather (Wiley, 2019)
The trophic magnification of polybrominated diphenyl ethers (PBDEs) and selected nonlegacy halogenated organic compounds (HOCs) was determined in the food web of Lake Ontario (ON, Canada). In all, 28 Br-3-Br-8-PBDEs and 24 HOCs (10 of which had not been targeted previously) were analyzed. Average concentrations of sigma 28PBDEs in fish ranged between 79.7 +/- 54.2 ng/g lipid weight in alewife (Alosa pseudoharengus) and 815 +/- 695 ng/g lipid weight in lake trout (Salvelinus namaycush). For invertebrates, concentrations were between 13.4 ng/g lipid weight (net plankton; >110 mu m) and 41.9 ng/g lipid weight in Diaporeia (Diaporeia hoyi). Detection frequency (DF) for HOCs was highest for anti-Dechlorane Plus (anti-DDC-CO), 1,3-diiodobenzene (1,3-DiiB), tribromo-methoxy-methylbenzene (ME-TBP), allyl 2,4,6-tribromophenyl ether (TBP-AE), pentabromocyclododecene (PBCYD), alpha+beta-tetrabromocylcooctane (TBCO), 2-bromoallyl 2,4,6-tribromophenyl ether (BATE), and pentabromotoluene (PBT; DF for all = 100% in lake trout). Tetrabromoxylene (TBX), dibromopropyl 2,4,6-tribromophenyl ether (TBP-DBPE), and syn-DDC-CO were also frequently detected in trout (DF = 70-78%), whereas 2,3,4,5,6-pentabromoethyl benzene (PBEB) was detected only in plankton. Several HOCs were reported in aquatic biota in the Great Lakes (USA/Canada) for the first time in the present study, including PBCYD, 1,3DiiB, BATE, TBP-DBPE, PBT, alpha + beta-TBCO, and ME-TBP. The Br4-6-BDEs (-47, -85, -99, -100, -153, and -154) all had prey-weighted biomagnification factors (BMFPW) values >6, whereas BMFPW values for Br7-8-BDEs were <1. The highest BMFPW values of non-PBDEs were for TBP-DBPE (10.6 +/- 1.34) and ME-TBP (4.88 +/- 0.60), whereas TBP-AE had a BMFPW value of <1. Significant (p <= 0.05) trophic magnification factors (TMFs), both positive and negative, were found for Br4-8-BDEs (BDE 196 = 0.4; BDE 154 = 9.5) and for bis(2,4,6-tribromophenoxy)ethane (BTBPE; 0.53), PBCYD (1.8), 1,3-DiiB (0.33), and pentabromobenzene (PBB; 0.25). Food chain length was found to have a significant influence on the TMF values. Environ Toxicol Chem 2019;38:1198-1210. (c) 2019 SETAC
Keywords: Flame retardants; Lake; Ontario; Lake Ontario; Biota; Biomagnification factor; Trophic magnification factor